2022
DOI: 10.1007/s40314-022-01957-5
|View full text |Cite
|
Sign up to set email alerts
|

On the Sombor characteristic polynomial and Sombor energy of a graph

Abstract: Let G be a simple graph with vertex set $$V(G) = \{v_1, v_2,\ldots , v_n\}$$ V ( G ) = { v 1 , v 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As a consequence, they have shown that the Petersen graph is determined uniquely by its domination polynomial. Ghanbari has studied the Sombor characteristic polynomial and Sombor energy of these graphs in [7], and has shown that the Petersen graph is not determined uniquely by its Sombor energy, but it has the maximum Sombor energy among others.…”
Section: Results For Certain Graphsmentioning
confidence: 99%
“…As a consequence, they have shown that the Petersen graph is determined uniquely by its domination polynomial. Ghanbari has studied the Sombor characteristic polynomial and Sombor energy of these graphs in [7], and has shown that the Petersen graph is not determined uniquely by its Sombor energy, but it has the maximum Sombor energy among others.…”
Section: Results For Certain Graphsmentioning
confidence: 99%
“…Statistical information on the research of graph energies and their applications is provided in [13]. [14] introduces the Sombor characteristic polynomial and the Sombor energy for some graph classes. In [15], the author establishes the relationship between energy and Sombor energy of the m-splitting graph and m-shadow graph of a k-regular graph.…”
Section: Introductionmentioning
confidence: 99%